2019
DOI: 10.1093/sleep/zsz093
|View full text |Cite
|
Sign up to set email alerts
|

Higher amounts of sedentary time are associated with short sleep duration and poor sleep quality in postmenopausal women

Abstract: Study Objectives To evaluate the associations between sedentary time, total (total-PA), light (light-PA), moderate (MOD-PA), and vigorous (VIG-PA) physical activity with indices of sleep in postmenopausal women. Methods Baseline self-reported data from the Women’s Health Initiative Observational Study (n = 75 074) were used in this cross-sectional analysis. Total-PA, light-PA, MOD-PA, and VIG-PA were categorized by metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 50 publications
3
26
0
1
Order By: Relevance
“…In line with our findings, a recent meta-analysis indicated no independent associations between SB and SQ but did demonstrate associations with other sleep outcomes [10]. More recent results from two large observational studies in generally healthy adults indicated that when the self-reported SB was high, the odds of reporting poor SQ/sleep problems nearly doubled [11,12]. Loprinzi et al examined data (N = 5563) from a large US sample of adults using objectively measured SB [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with our findings, a recent meta-analysis indicated no independent associations between SB and SQ but did demonstrate associations with other sleep outcomes [10]. More recent results from two large observational studies in generally healthy adults indicated that when the self-reported SB was high, the odds of reporting poor SQ/sleep problems nearly doubled [11,12]. Loprinzi et al examined data (N = 5563) from a large US sample of adults using objectively measured SB [7].…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis found SB to be associated with an increased risk of insomnia and sleep disturbance but not daytime sleepiness and poor SQ in adults [10]. More recent results from observational studies suggest an independent relationship with SB and SQ [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This could potentially limit the effectiveness of an exercise program to further improve sleep as those that are more active tend to have less sleep disturbance at baseline than those who are inactive. 36 Second, there was no control group. This limits the ability to determine whether a clinic-based exercise program was more effective than standard of care (e.g., “nothing”) for improving sleep, or to control for the effect of time (i.e., does sleep improve as participants move further from completing chemotherapy and/or radiation treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Walking at 3.0 mph requires 3.5 METs of energy expenditure, which is considered a moderate‐intensity activity 13 . Thus, to be consistent with PAGA recommendations and previous studies, the total physical activity variable in MET‐hours/week was calculated and divided into four categories (0, >0‐7.4, 7.5‐14.9 and ≥15 MET‐hours/week) (15 MET‐hours/week was calculated by considering 6.0 × 150 minutes/week/60 = 15 MET‐hours/week as the upper scale of the recommendation level), 29 the walking specific activity variable was categorized as 0, >0‐8.74 and ≥8.75 MET‐hours/week (8.75 is derived as follows: 3.5 METs × 2.5 hours), and the moderate to vigorous‐intensity physical activity (MVPA) variable was derived from recreational physical activity, which was then categorized as into 0, >0‐11.24 and ≥11.25 MET‐hour/week (11.25 was calculated as the midpoint of the range 7.5 to 15 MET‐hours per week) 13,29 …”
Section: Methodsmentioning
confidence: 95%